VEXAS syndrome: A review on clinical manifestations - Roy, Bedanta; Othieno, Juliet; Fauzee, Nabeeha (Journal of Biomedical Sciences, 2023)
Background: VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) syndrome is a recently identified progressive, adult-onset, inflammatory disorder. Somatic mutations in the Ubiquitin-like modifier activating enzyme 1 (UBA1) gene at methionine-41 (p. Met41) were found in the patients. Clinical presentations are not limited to hematological and immunological systems; all organ systems are affected by VEXAS syndrome. The aim of this review is to summarise the scientific evidence accrued from the research studies on VEXAS syndrome, highlighting the clinical features and involvements of different organ systems. Conclusion: Although the primary manifestations affect the immunological and haematological systems, they gradually affect different other organ systems. Distinct clinical features necessitate ruling out the other possibilities that will be helpful for early diagnosis. More research should be carried out by the global research community in a collaborative manner for a better understanding and early diagnosis of the syndrome.